PENGARUH INSENTIF DAN BONUS TERHADAP SEMANGAT KERJA KARYAWAN PADA KOPERASI CU. DOSNITAHI PINANGSORI KABUPATEN TAPANULI TENGAH - Hibur Hati Tafonao; Kaharuddin Kaharuddin; Rosmita Ambarita (KOLONI, 2022)
This study aims to determine whether there is an influence of incentives and bonuses on employee morale in CU cooperatives. Dosnitahi Pinangsori, Central Tapanuli Regency. This research uses a type of quantitative descriptive research. the research data is normally distributed because the histogram graph is in the shape of a bell, on the P-P plot graph you can see the distribution of data close to the diagonal line and the results of the Kolmogorov-Smirnov statistical test show a sig value greater than 0.05, which means that all data used in this study is distributed normal. From the multicollinearity test, it is known that the tolerance value is <0.1 and the variance inflation factor (VIF) value is <10. It can be concluded that the regression model found a correlation between independent variables. From the heteroscedasticity test it is known that the distribution of the dots does not form a specific pattern and the dots spread above and below the zero on the Y axis, it can be stated that there is no heteroscedasticity problem. The results of the multiple regression test obtained Y = 11,023 + 0.166 + 0.636 X. This means that the effect of the dependent variable (work morale) is determined by the independent variable (incentives and bonuses) with a regression coefficient of 0.166 and 0.636 where if one unit of X variable or value is added certain then the variable Y (work enthusiasm) will also increase multiplied by that certain value. From the t test, it is obtained that the calculated t value of incentives and bonuses is greater than the t table value and from the F test it is obtained that the calculated F value is greater than the F table value. Based on the results of the t and ji F tests obtained, it can be concluded that the hypothesis proposed in this study can be "accepted". Keywords: incentives, bonuses, and morale